Recent development of innovative methods for efficient frying technology. Issue 22 (16th December 2021) - Devi, Shoma; Zhang, Min; Ju, Ronghua; Bhandari, Bhesh
Abstract: Deep-frying is the century-old and the most common cooking process which is still being used to prepare a variety of food products in industrial and domestic scales. Compared to other cooking processes, frying produces some distinctive flavor characteristics, but other undesirable and unacceptable characteristics to consumers are also originated during frying. Researchers have taken various technical approaches for reducing the oil content of fried products without compromising product quality. This review discusses some recently developed frying techniques which could improve the product quality, and advance frying efficiency, to save energy cost. Some modified method of alternative frying technologies used by the researchers are vacuum frying, microwave frying, microwave-assisted vacuum frying, radiant frying, ultrasound treated frying, air frying or their combinations. In this review, we aim to give a detailed insight into some specific aspects of new deep-frying practices and pretreatments for the quality maintenance of fried products highlighting their novelty and efficiency.